2022
DOI: 10.3390/su14031790
|View full text |Cite
|
Sign up to set email alerts
|

Co-Selection of Heavy Metal and Antibiotic Resistance in Soil Bacteria from Agricultural Soils in New Zealand

Abstract: Accumulation of trace elements (including heavy metals) in soil from usage of superphosphate fertilisers induces resistance of soil bacteria to trace elements of environmental concern (TEoEC) and may co-select for resistance to antibiotics (Ab). This study aimed to investigate selection of co-resistance of soil bacteria to Cd, Zn and Hg, and Ab in soils with varied management histories. Genetic diversity of these bacteria and horizontal transfer of Cd resistance genes (cadA and czcA) were also investigated. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…This was reinforced by the bacteria's multiple antibiotic resistance indices, which were>2, suggesting exposure of the isolates to antibiotic contamination (Matyar et al, 2014). Similarly, the bacteria resistance to both heavy metals and antibiotics in the wastewater confirms that resistance factors for heavy metals and antibiotics are coselected in heavy metal-contaminated systems or habitats exposed to anthropogenic pressure (Timoney et al, 1978;Bhattacherjee et al, 1988;Baker-Austin et al, 2006;Heydari et al, 2022).…”
Section: Discussionmentioning
confidence: 94%
“…This was reinforced by the bacteria's multiple antibiotic resistance indices, which were>2, suggesting exposure of the isolates to antibiotic contamination (Matyar et al, 2014). Similarly, the bacteria resistance to both heavy metals and antibiotics in the wastewater confirms that resistance factors for heavy metals and antibiotics are coselected in heavy metal-contaminated systems or habitats exposed to anthropogenic pressure (Timoney et al, 1978;Bhattacherjee et al, 1988;Baker-Austin et al, 2006;Heydari et al, 2022).…”
Section: Discussionmentioning
confidence: 94%
“…This inference is supported by the results of the correlation analyses. Several reports have indeed indicated that this co-selection phenomenon has often been triggered by the presence of metals [4,[64][65][66][67][68][69]. This is an alarming discovery as the potential spread to residential areas via bioaerosols is indicated by the presence of resistant coliforms in the indoor and outdoor air of nearby homes and shops.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, the cost is placed at £ 1.4 billion yearly while in developing countries, estimates are hard to come by as health care is largely privately funded [ 9 ]. More complicated is the fact that these ARGs have been shown to co-evolve with heavy metal resistance genes [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic resistance genes occur naturally in various environments in low abundance. However, studies have shown that their abundance increase in the presence of several pollutants such as heavy metals, crude oil and sewage [ 10 , 11 , 18 ]. Where this happens, these ARG can move from one microorganism to another via horizontal and vertical mechanisms triggering multi-drug resistance and compounding clinical outcomes of infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation